Scientific creativity of secondary school students on colloid system - Nursiwan, Wimbi Apriwanda; Hanri, Chuzairy; Ibrahim, Nor Hasniza (Eclética Química, 2025)
The significance of scientific creativity in science has been highlighted for nearly two decades. In chemistry education, this involves students’ ability to generate concepts related to chemical problems and phenomena, such as the colloid system found in daily life. Understanding the colloid system requires students to produce scientific ideas for problem-solving. Therefore, assessing students’ scientific creativity is crucial. This research aimed to determine students’ scientific creativity concerning the colloid system using a descriptive, quantitative approach. Seventy-six students were selected through simple random sampling. Data collection involved four open-ended questions, analyzed using a scoring rubric and percentage scores. The study revealed that students’ fluency, flexibility, and originality were low, leading to unsatisfactory results in questions requiring divergent thinking and scientific imagination. These findings highlight the need to enhance students’ ability to generate scientific ideas, emphasizing the importance of fostering scientific creativity in education.